The potential role of the carotid body in COVID-19 - Porzionato, Andrea (Am J Physiol Lung Cell Mol Physiol, 2020)
The carotid body (CB) plays a contributory role in the pathogenesis of various respiratory, cardiovascular, renal, and metabolic diseases through reflex changes in ventilation and sympathetic output. On the basis of available data about peripheral arterial chemoreception and severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2), a potential involvement in the coronavirus disease 2019 (COVID-19) may be hypothesized through different mechanisms. The CB could be a site of SARS-CoV-2 invasion, due to local expression of its receptor [angiotensin-converting enzyme (ACE) 2] and an alternative route of nervous system invasion, through retrograde transport along the carotid sinus nerve. The CB function could be affected by COVID-19-induced inflammatory/immune reactions and/or ACE1/ACE2 imbalance, both at local or systemic level. Increased peripheral arterial chemosensitivity and reflex sympatho-activation may contribute to the increased morbidity and mortality in COVID-19 patients with respiratory, cardiovascular, renal, or metabolic comorbidities.